Für wen schreibt Kant und warum? Kants Haltung als philosophischer Schriftsteller in seinen Vorreden - Johst, Sandra Eleonore (Studia Kantiana, 2023)
The following discussion aims to present Kant's reflections and intentions in relation to his philosophical writing. His writings include academic qualification papers that were originally written in Latin, the transcendental-philosophical Critiques, for which he developed his own terms, and accessible essays devoted to contemporary topics and questions. On the basis of his explicit statements in the prefaces, an understanding of philosophy as a joint project of scholars is asserted, which requires a certain attitude on the part of those who are involved. The basic lines of this attitude are outlined by an exegesis of the prefaces, focusing firstly on the functions of the author, secondly on those of the reader and thirdly on the writings. The developed self-image of Kant as a philosophical author illustrates the Enlightenment understanding of philosophy: With joint progress in science, we can also promote cultural progress for humanity and achieve benefits in the world.